Adaptive Learning Programs: Fostering Continuous Skill Development in the Workplace - Atmaja, Hanung Eka; Pane, Musa Darwin; Kurniawan, Rano (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research investigates the dynamics of adaptive learning programs in fostering continuous skill development among employees within the organizational context of PT Usaha Jaya. Through a quantitative research design and Structural Equation Modeling with Partial Least Squares (PLS) analysis, the study examines the direct and indirect effects of adaptive learning programs and workplace environment on employee engagement and subsequent skill development. The findings reveal significant direct effects of adaptive learning programs on both employee engagement and continuous skill development, underscoring the efficacy of personalized learning initiatives in enhancing employee commitment and skill acquisition. Moreover, the indirect effect analysis demonstrates a significant pathway from adaptive learning programs to continuous skill development through employee engagement, emphasizing the mediating role of employee engagement. However, the influence of workplace environment on continuous skill development through employee engagement was found to be nonsignificant, suggesting that other factors may play a more prominent role in shaping the relationship between employee engagement and skill development. These results provide valuable insights for organizations seeking to optimize workforce development strategies and drive organizational success in dynamic business environments.